Manajemen K3, Keamanan Fisik, & Kondisi Kerja: Pengaruhnya terhadap Produktivitas Pekerja (Studi pada Dua Perusahaan Tekstil Terkemuka di Jawa Timur) - Azzuhri, Misbahuddin (Jurnal Aplikasi Manajemen, 2008)
Occupational safety and health (OSH) is considered a part of human rights. A company disregarding to the OSH issues would obtain bad image which may weaken the company's market power. Besides, the company should pay attention to environment issues. By integrating comprehensively OSH and environment issues in its strategy and policy, the company may obtain some benefits, especially which have related to worker productivity. The research objectives were (1) examining the effect of OSH management. physical security, and working condition on worker productivity simultaneously, (2) examining the effect of OSH management, physical security, and working condition on worker productivity partially. The research design was conducted by using observational and cross-sectional data toward 179 respondents of the workers at PT Easternter and PT Paberik Tekstil Kasrie. The data collecting was conducted, by using questionnaire and also supported by secondary data. The data analysis was conducted, by using Exploratory Factor Analysis and Multiple Regression Analysis. To guarantee accuracy of statistical finding the research also present results of labor utilization rate (LUR) and labor productivity index. Result of multiple regression analysis revealed that OSH management, physical security, and working condition had impact on worker productivity simultaneously and partially. And partially, three independent variables also have impact on worker productivity for PT. Easterntex, except OSH management which had no impact on worker productivity for PT Paberik Tekstil Kasrie significantly. Result for PT Paberik Tekstil Kasrie actually similar to textile industry context.